Pengaruh Suhu Co-Pyrolysis Limbah Ban Bekas Dan Tandan Kosong Sawit Terhadap Yield Bio-Oil - Nasution, Ahmadani; Sunarno, Sunarno; Saputra, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The decline in fossil fuel sources encourages research to find alternative fuels. One of the efforts currently being to find alternative energy sources that have high efficiency and environmental friendly is bio-oil from empty fruit bunches (EFB) and tire waste. This research aims to determine effect of temperature co-pyrolysis of EFB and tire waste on yield bio-oil and then characterize the physics at the highest yield. In this study, the ratio of EFB/tire (R) was 25/75 with an operating temperature of 400°C, 450°C, 500°C, 550°C and 600°C which supplied nitrogen gas of 200 ml/minute for 90 minutes. Bio-oil with highest yield obtained from a temperature of 500°C ie 44.3% with density, viscosity, calorific value, and degree of acidity (pH), respectively 0.994 g/ml, 1.53 cSt, 40.31 MJ/kg and pH 3.39. Keywords: alternative energy, bio-oil, co-pyrolysis, EFB, tire